English Teachers’ Perception on the Use of EMI in Public Schools - Neupane, Maniram (Janajyoti Journal, 2025)
This research article examines the perceptions of English language teachers regarding the use of English as a medium of instruction (EMI) in public schools of Nepal. It aims to explore and disseminate the findings of English language teachers' perceptions of implementing EMI, especially in secondary schools. The narrative inquiry method was employed within the framework of the interpretative research paradigm. Within Nepal, some teachers and students preferred EMI, whereas most of the students and teachers liked and demanded the use of the mother tongues of the students. They urge multilingualism, at least bilingualism (the use of learners' mother tongues), facilitates the learning of L2 more than the use of a monolingual strategy. I have found from this study that we had better let the learners select the medium of instruction on their own. It can contribute to the learning of an L2, in three perspectives: by making the learners learn easily with a clear concept of the content; by reducing costs for materials and training for implementing the EMI, and, most importantly, by preserving the local language and culture of the people, ultimately their identity. It also keeps the way open for the use of the target language in the classrooms if the learners prefer. So, I emphasize the 'Learners' Preference Theory (LP Theory)'. The learners should be the center of the teaching learning process, and they should understand the content that is delivered. Not only this, our language, culture, and identity should also be preserved, and we should be aware that we may not be lost after a few decades.